A variação linguística em sala de aula: uma proposta de intervenção reflexiva sobre o preconceito linguístico - Araujo, Maria Jose Oliveira (2014)
This paper has the main propose to present a reflection on the different ways of speaking at school Focuses respect to variations of the Portuguese without prejudice and seeks to contribute to improving the teaching of the mother tongue. To implement this action research study , we rely on the Theory Sociolinguistics Variationist initiated by Labov, which triggered proposals for language teaching , guided by the correlation between language and society , as well as contributions to the teaching of the mother tongue in this theoretical context , and Brazilian scholars as Bortoni-Ricardo (2005, 2008), Marcos Bagno (2005, 2007) , among others. The participating class of this study are students of the 5th year of the Schools of Municipal Schools in the city of João Pessoa. With the focus on the principle of heterogeneity of language focuses our pedagogical actions of interactional character in the classroom, to reflect on the "appropriate" and "not appropriate " in regard to language as a communication situation. Thus, we seek to present oral and written cultural norms for students with defined criteria and methods that lead to reflection and not allow prejudice, as we believe, with language, is also socially. We hope through this study has raised a new look at linguistic prejudice, that it can gradually be minimized in society, and is the school that this work should start in the search for a society where there is no more people who are stigmatized for their use speech . Experience has shown that working with linguistic variation, focusing on combating linguistic prejudice, can be an effective teaching tool, as a new proposal for teaching the English language according to the PCN seeks greater linguistic awareness.